PEMIKIRAN PENDIDIKAN ISLAM AHMAD SYAFII MAARIF - Mohamad Ali (Profetika: Jurnal Studi Islam, 2016)
The Indonesian Islamic intellectualism is increasingly dynamic and accounted in the global arena. This perception occurs because on the one hand, Indonesia is the largest concentration of Muslim population in the world, and on the other side there is an ontentic, dynamic and inclusive process of Islamic intellectualism. The 1980s Indonesian Islam gave birth to a series of "new intellectuals" whose ideas contributed significantly to embroidering the Indonesian pillars of social progress and justice: the Islamization, nationalism, humanity and modernity. One of the pioneers of new intellectualism worth taking into account is Ahmad Syafii Maarif. He is widely known as an Islamic thinker as well as a social activist involved in solving national and humanitarian issues. So far, the public recognizes Buya Syafii as a Muslim historian and intellectual who devotes his enormous intellectual energy to builds an inclusive Islamic culture. Beyond, there is one dimension of Buya Syafii's idea that is almost oblivious to the public's attention, namely the spark of his thoughts on Islamic education which is driven concern over the social reality of Islamic education which is dichotomous, backward, and poor in thought.The thought of Buya Syafii is intended to find a way out of the crisis of Islamic education from the "trap" of history, namely by redialog with the Qur'an. Hypothetically, Islamic education thought he borrowed, patterned religious-critical.Geliat intelektualisme Islam Indonesia semakin dinamis dan diperhitungkan di kancah global. Persepsi ini terjadi karena di satu sisi, Indonesia merupakan tempat konsentrasi penduduk Muslim terbesar di dunia, dan di sisi lain ada proses pertumbuhan intelektualisme Islam yang ontentik, dinamis dan inklusif. Dekade 1980-an Islam Indonesia melahirkan sederet “intelektual baru” yang ide-idenya berkontribusi signifikan dalam menyulam pilar-pilar Indonesia berkemajuan dan berkeadilan sosial, yaitu: ke-Islaman, kebangsaan, kemanusiaan, dan kemodernan. Salah satu pelopor intelektualisme baru yang layak diperhitungkan adalah Ahmad Syafii Maarif. Dia dikenal luas sebagai pemikir Islam sekaligus aktivis sosial yang terlibat dalam upaya pemecahan persoalan kebangsaan dan kemanusiaan. Sejauh ini, publik mengenal sosok Buya Syafii sebagai seorang sejarawan dan cendekiawan Muslim yang mencurahkan energi intelektualnya yang begitu besar untuk membangun kultur Islam inklusif. Di luar itu, ada satu dimensi pemikiran Buya Syafii yang hampir luput dari perhatian publik, yaitu percikan pemikirannya tentang pendidikan Islam yang digerakkan keprihatinan atas realitas sosial pendidikan Islam yang dikotomik, terbelakang, dan miskin pemikiran. Pemikiran Buya Syafii ditujukan untuk mencari jalan keluar atas kemelut pendidikan Islam dari “jebakan” sejarah, yakni dengan mendialogkannya kembali dengan Al-Qur’an. Secara hipotetik, pemikiran pendidikan Islam yang diusungnya bercorak kritis-religius.